2019
DOI: 10.1016/j.jdiacomp.2019.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Undiagnosed coronary artery disease in long-term type 1 diabetes. The Dialong study

Abstract: Aims: We studied the total prevalence of obstructive coronary artery disease (CAD), undiagnosed CAD and absent CAD in persons with ≥45-year duration of type 1 diabetes (T1D) versus controls, and associations with mean HbA 1c , LDL-cholesterol and blood pressure over 2-3 decades. Methods: We included 76% (n=103) of all persons with T1D diagnosed ≤1970 attending a diabetes center and 63 controls without diabetes. We collected 20-30 years of HbA 1c , LDLcholesterol and blood pressure measurements. Participants wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 41 publications
(36 reference statements)
1
24
0
1
Order By: Relevance
“…Computed tomography coronary angiography (CTCA) is increasingly employed to detect CVD. A recent study demonstrated a high prevalence of undiagnosed obstructive coronary artery disease in patients with T1DM of long duration, with an association with mean HbA1c [ 81 ]. CTCA can also be used to generate CAC scores.…”
Section: Surrogate Measurements Of Atherosclerosis: Screening and Detmentioning
confidence: 99%
“…Computed tomography coronary angiography (CTCA) is increasingly employed to detect CVD. A recent study demonstrated a high prevalence of undiagnosed obstructive coronary artery disease in patients with T1DM of long duration, with an association with mean HbA1c [ 81 ]. CTCA can also be used to generate CAC scores.…”
Section: Surrogate Measurements Of Atherosclerosis: Screening and Detmentioning
confidence: 99%
“…and lower diastolic blood pressure than the control group [4]. Five percent in the diabetes group had no retinopathy.…”
Section: Plos Onementioning
confidence: 65%
“…The accelerated coronary atherosclerosis seen in diabetes is more severe and diffuse than in people without diabetes [1][2][3]. However, some people have normal coronary arteries after 50 years of type 1 diabetes as we have recently reported [4].…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations